The silent geriatric giant- anxiety disorders in late life - Nowshin, Iffat; Kabir, Farhana (Bangladesh Journal of Physiology and Pharmacology, 2014)
Late-life anxiety can often be silent, missed or difficult to diagnose as older adults tend to somatize psychiatric problems. Yet late-life anxiety disorders are a "geriatric giant," being twice as prevalent as dementia among older adults and four to eight times more prevalent than major depressive disorders, causing significant impact on the quality of life, morbidity, and mortality of older adults. Bangladesh is one of the twenty countries in the world with the largest elderly population and by 2025, along with four other Asian countries, will account for 44% of world's total elderly population. Demographic and epidemiological transitions reveal geriatric problems as burning public health issue. So more emphasis should be given on geriatric health problems in order to ensure physical, mental and socially sound health. http://dx.doi.org/10.3329/bjpp.v29i1-2.20065 Bangladesh J Physiol Pharmacol 2013; 29(1&2) : 29-31